2015
DOI: 10.1111/trf.13252
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency anemia at admission for labor and delivery is associated with an increased risk for Cesarean section and adverse maternal and neonatal outcomes

Abstract: Iron deficiency anemia at delivery is associated with an increased risk for cesarean section and adverse maternal and neonatal outcomes in otherwise healthy women. Monitoring/correction of hemoglobin concentrations even in late pregnancy may prevent these adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
136
6
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(165 citation statements)
references
References 46 publications
8
136
6
15
Order By: Relevance
“…It has been shown that approximately 10.5% of women in the Helsinki area in Finland have iron deficiency anemia when they present for delivery (44). Iron deficiency anemia puts the mother at higher risk during childbirth, and she also has a higher risk of post-partum infections.…”
Section: Added Health Benefits Of Hormonal Contraceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that approximately 10.5% of women in the Helsinki area in Finland have iron deficiency anemia when they present for delivery (44). Iron deficiency anemia puts the mother at higher risk during childbirth, and she also has a higher risk of post-partum infections.…”
Section: Added Health Benefits Of Hormonal Contraceptionmentioning
confidence: 99%
“…Anemia may also impact on the ability to breastfeed (45,46). In the Finnish register study (44) anemia at presentation for delivery was associated with a higher risk for pre-term delivery, cesarean section, and neonatal intensive care admission of the newborn. Post-partum anemia is also linked to post-partum depression, reduced quality of life, and reduced cognitive abilities (46).…”
Section: Added Health Benefits Of Hormonal Contraceptionmentioning
confidence: 99%
“…Maternal IDA is associated with increased risk for cesarean delivery, transfusion, perinatal bleeding, preeclampsia, placental abruption, poor maternal thyroid status, poor wound healing, cardiac failure, and even death [11, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…IDA in pregnancy may also contribute to poorer cognitive development and IDA among children (Radlowski and Johnson 2013), and has been implicated in the development of post-partum depression (Albacar et al 2011). A recent study showed that IDA was an independent risk factor for maternal transfusion, preterm delivery, 5 min APGAR less than seven, and NICU admission (Drukker et al 2015), and associated a 1 g/dL increase in hemoglobin with an approximate 8% decrease in risk for Cesarean section (Drukker et al 2015). Most cases of IDA are easily treated by dietary supplementation when identified (Johnson-Wimbley and Graham 2011).…”
Section: Introductionmentioning
confidence: 99%